The Effect of Tprc Strategy on Students Ability in Reading Comprehension Descriptive Text to The Eighth Grade at SMP Negeri 10 Pematangsiantar - Andrian Laris Nadeak; Asima Rohana Sinaga; Christian Neni Purba (The Future of Education Journal, 2024)
The purpose of this research is to investigate the effect of the TPRC strategy on students' reading comprehension of descriptive text in eighth grade at SMP Negeri 10 Pematangsiantar. This investigation was conducted at SMP Negeri 10 Pematangsiantar, namely in classes VIII-2 and VIII-3. The research issue is about the impact of the TPRC Strategy as a teaching medium on reading comprehension descriptive texts for class VIII students at SMP Negeri 10 Pematangsiantar. The researchers employed quantitative descriptive research methodologies in a quasi-experimental design with two classes: experimental and control. Multiple choice exams were used to acquire the data. The data collection instruments were collected from students' pre-test and post-test results; scores were then computed and assessed using MS Excel and manual. The study findings revealed that the experimental class had an average pre-test score of 57.96 and a post-test score of 80.8. Meanwhile, the control class had an average score of 61.09 before the exam and 71.40 after the test. The post-test findings demonstrate that the usage of TPRC learning medium is extremely helpful for class VIII students' reading comprehension of descriptive texts. The t-test computation reveals that the t-test result exceeds the t-table value (2.13 > 1.669). At a 5% significance level, a two-sided test indicates that the null hypothesis (HO) is rejected and the alternative hypothesis (Ha) is accepted. This suggests that the use of the TPRC Strategy as a teaching medium may help students enhance their reading comprehension.